Coordinated tracking for networked robotic systems via model-free controller–estimator algorithms. Issue 13 (September 2017) - Ge, Ming-Feng; Xiong, Cai-Hua; Liu, Zhi-Wei; Liu, Jie; Zhao, Xiao-Wen
Abstract: This paper mainly focuses on two classes of coordinated tracking problems for networked robotic systems, including semi-global coordinated tracking (SCT) problem and global coordinated tracking (GCT) problem. Considering that the dynamics of the networked robotic system can be unattainable, several novel model-free controller-estimator algorithms are proposed to solve the SCT and GCT problems, as well as to reject the input disturbances contained in the system dynamics. By invoking nonsmooth analysis and Lyapunov argument, a number of novel criteria (including sufficient criteria, necessary and sufficient criteria) for semi-global and global asymptotic stability of the presented algorithms are established. Finally, simulation experiments are carried out to verify the theoretical results.